The Romanian political novel of the 1960s and 1970s (Colloquia Comparativa Litterarum, 2025)
Joanna Slavcheva. The Romanian Political Novel of the 1960s and 1970s. Veliko Tarnovo, St. Cyril and St. Methodius University Press, 2022.